ZjFAS2 is involved in the fruit coloration in Ziziphus jujuba Mill. by regulating anthocyanin accumulation - Li, Shipeng; Shen, Yuanyuan; Zheng, Shipei; Zhu, Qihang; Cai, Linfang; Wang, Yian; Zhao, Xusheng (Frontiers in Plant Science, 2023)
Fruit color is one of the most important traits of jujube (Ziziphus jujuba Mill.). However, the differences in the pigments of different varieties of Jujube are not well studied. In addition, the genes responsible for fruit color and their underlying molecular mechanisms remain unclear. In this study, two jujube varieties, namely “Fengmiguan” (FMG) and “Tailihong” (TLH), were considered. These cultivars differed in color owing to their respective anthocyanin accumulation patterns. Three and seven types of anthocyanins were found in FMG and TLH, respectively, which played a key role in the process of fruit coloration. Transcriptome and quantitative reverse transcription polymerase chain reaction analyses indicated that ZjFAS2 expression was significantly and positively correlated with the total anthocyanin content. The overexpression and transient expression experiments confirmed that ZjFAS2 positively regulates anthocyanin accumulation. The expression profile of ZjFAS2 exhibited its different expression trends in different tissues and varieties. Subcellular localization experiments showed that ZjFAS2 was localized to the nucleus and membrane. A total of 26 interacting proteins were identified, and the possibility of ZjFAS2 interacting with ZjSHV3 to regulate jujube fruit coloration was studied. Herein, we investigated the role of anthocyanins in the different coloring patterns of the jujube fruits and provided a foundation for elucidating the molecular mechanism underlying jujube fruit coloration.